Mesoscale and microscale shock effects in the LL6 S4 chondrites Saint‐Séverin and Elbert: A tale of two breccias. (31st May 2019) - Hugo, Richard C.; Ruzicka, Alex M.; Rubin, Alan E.
Abstract: Saint‐Séverin and Elbert, two LL6 chondrite breccias, were systematically studied to evaluate multiple deformation effects on spatial scales ranging from thin section (mesoscale) to micron‐submicron (microscale) using optical microscopy, electron backscatter diffraction (EBSD), and transmission electron microscopy (TEM). The different techniques provide consistent results but have complementary strengths, together providing a powerful approach to unravel even complex impact histories. Both meteorites have an S4 conventional shock stage, but interclast areas are more deformed, and clasts are more deformed in Elbert than in Saint‐Séverin. TEM and EBSD data provide compelling evidence that Saint‐Séverin experienced significant shock deformation while already hot, and cooled rapidly afterward, as a result of a major, possibly disruptive impact on the LL chondrite parent body 4.4 Ga ago. In contrast, Elbert was shocked from a cold initial state but was heated significantly during shock, and cooled in a localized hot impact deposit on the LL asteroid. Both meteorites probably were shocked at least twice; data for Saint‐Séverin are best reconciled with a three‐impact model.